A case of Cauda Equina syndrome in a leukemic patient due to intrathecal methotrexate - (:unkn) unknown (My University, 2007)
The leukemias may cause neurologic dysfunction through either direct invasion of the nervous system or indirectly through cytopenias, or it may occur as a result of the necessarily vigorous treatment programs for leukemia. We report here a 24-year-old acute lymphoblastic leukemia patient who in her second cycle of hyper-CVAD chem therapy regimen (high-dose Ara-C and high-dose methotrexate) received intrathecal methotrexate and two days afterwards was diagnosed as having Cauda Equina syndrome (CES). A lumbo-sacral MRI imaging with gadolinium was performed and there was a remarkable enhancement in the Cauda Equina region, suggesting either leukemic involvement or a type of neurologic complication associated with intrathecal methotrexate treatment. To rule out leukemic involvement, a lumbar puncture was performed and the CSF was free of leukemic cells. There are cases of CES developing after spinal anesthesia reported in the literature, but this is the first report of CES due to intrathecal methotrexate. © Turkish Society of Hematology.
Keywords: Acute lymphoblastic leukemia; Cauda Equina syndrome; Complication; Intrathecal methotrexate